(untitled) (Global Journal of Management and Business Research, 2021)
Introduction The technological advancement has changed the way people live their life such as communication travel learning and shopping The health sector was also influenced by the technological changes Objectives The objective of this study is to develop a model on consumer adoption on electronic health e-health in Malaysia Methods Extending the Technology Acceptance Model TAM with Personal Innovativeness in IT and Social Influence This paper presents the conceptual foundation on the adoption of e-health among young adults in Malaysia